2017
DOI: 10.1002/ece3.3439
|View full text |Cite
|
Sign up to set email alerts
|

Trait‐abundance relation in response to nutrient addition in a Tibetan alpine meadow: The importance of species trade‐off in resource conservation and acquisition

Abstract: In competition‐dominated communities, traits promoting resource conservation and competitive ability are expected to have an important influence on species relative abundance (SRA). Yet, few studies have tested the trait‐abundance relations in the line of species trade‐off in resource conservation versus acquisition, indicating by multiple traits coordination. We measured SRA and key functional traits involving leaf economic spectrum (SLA, specific leaf area; LDMC, leaf dry matter content; LCC, leaf carbon con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
(66 reference statements)
1
10
1
Order By: Relevance
“…When analyzing the investment in morphometric characteristics, we noticed that C. pyramidale and L. ferrea seedlings showed better quality when planted without coconut fiber or powder, achieving larger specific leaf areas. This characteristic is related to the higher acquisition of resources from the environment [35,36]. In the field, seedlings with a larger specific leaf area can benefit from being more effective in mitigating the negative impacts of rain [37], as well as having high water content, and carrying out high photosynthesis rates [38].…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing the investment in morphometric characteristics, we noticed that C. pyramidale and L. ferrea seedlings showed better quality when planted without coconut fiber or powder, achieving larger specific leaf areas. This characteristic is related to the higher acquisition of resources from the environment [35,36]. In the field, seedlings with a larger specific leaf area can benefit from being more effective in mitigating the negative impacts of rain [37], as well as having high water content, and carrying out high photosynthesis rates [38].…”
Section: Discussionmentioning
confidence: 99%
“…Theory postulates that species with intermediate trait values are the most abundant ones, because these species are those that are best adapted to the specific environmental conditions and may have the highest competitive ability (Grime, 2006;Laughlin et al, 2012;Rolhauser et al, 2019). However, solid empirical evidence for an unimodal relationship between species mean traits and abundance remains scarce with studies reporting linear and/ or opposing relationships (Cornwell & Ackerly, 2010;Lauterbach et al 2013;Liu et al, 2017;Read et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, solid empirical evidence for an unimodal relationship between species mean traits and abundance remains scarce with studies reporting linear and/or opposing relationships (Cornwell & Ackerly, 2010; Lauterbach et al. 2013; Liu et al., 2017; Read et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The general view is that environmental conditions drive optimal trait combinations, which can affect species abundance [19,20]; therefore, changes in environmental factors can lead to shifts in the given trait-abundance relationships (not only a shift in the slope but given Diversity 2021, 13, 569 2 of 9 trait-abundance relationships can also appear or disappear) [10,17]. For example, a study in a Tibetan alpine meadow community showed that a significant correlation between leaf dry matter content (LDMC) and abundance appeared [21] while the significant correlation between specific leaf area (SLA) and abundance disappeared under long-term phosphate addition [22]. Thus, it is essential to test whether the specific trait-abundance relationships still exist under different environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that species with traits related to rapid resource acquisition become dominant under added soil resources, whereas those related to resource conservation have superiority under lower soil resource availability [25]. The relationships between traits and abundance may vary because they mirror different aspects of species performance under changing conditions [22,26,27]. However, how nitrogen addition affects the relationships between traits and abundance remains uncertain, especially in desert ecosystems.…”
Section: Introductionmentioning
confidence: 99%